(Self) Manifesting. Eleven exercises for education (Praxis Educativa, 2018)
A manifesto is a public declaration of principles and intentions that presents ideas or problems in a conclusive and intensive manner through a text which admits diverse interpretations. Departing from the reading of A Manifesto For Education, released in 2010 by Gert Biesta and Carl Anders Säfström, reflect and manifest in regard to some of the aspects of this document which remain up to date after ten years in a current context of crisis/agony of education and the school system, as some argue. Eleven exercises are presented  which manifest resistances, piercings and meanings in a diverse range of interpretational acts: :  Gert Biesta y Carl Anders Säfström Mario Di Paolantonio, Sebastián Plá, José Yuni & Claudio Urbano, Rodrigo Matos de Souza, Ricardo Castaño Gaviria & Elizeu Clementino de Souza, José Tranier, Nilda Alves, Virginia Louzada, Claudia Chagas & Alessandra Nunes Caldas, Julieta Armella, Silvia Grinberg & Luis Porta
Keywords: manifesto; education; interpretational acts